Building Partnership Network in Viewing of Manager of Nonformal Educational Institution - Latief, Suryawahyuni; Hendrayani, Santi; Samsuddin, Samsuddin (Journal of Nonformal Education, 2022)
Building a network of partnership in the management of educational institutions is one thing that is very important to be done by the managers of non-formal educational institutions that are managed independently by the community so that the purpose of establishing non-formal educational institutions can be achieved.  This study aims to explore how the views of non-formal education managers and the forms of partnership built by non-formal education managers build partnership networks and obstacles faced in building partnership networks. This research uses qualitative methods and data collection is carried out by observation in the form of direct observations to several non-formal educational institutions located in three regions of Jambi province, namely Batanghari, Merangin, and Muaro Bungo. Interviews were conducted with non-formal education managers in three regions, as well as documentation in the form of visions, missions of non-formal educational institutions, cooperation documents, and some literature related to the management of non-formal education. The data that has been collected is analyzed and tested for validity using the source data trianggulation technique. The results showed that the managers of non-formal education units have similar views on the importance of cooperating in the management of non-formal education units, and the form of cooperation carried out in the form of cooperation in terms of financing, borrowing facilities and infrastructure, as well as resource persons for training and learning activities. The obstacles faced come from within the manager himself, namely still passive and less proactive in building partnership networks with other parties. The results of this study show that the managers of non-formal education units view building partnership networks only limited to practical matters, namely financing, borrowing facilities, and resource persons only in accordance with current needs, it is hoped that the results of the research will be able to improve the quality of management of non-formal educational institutions managed by the community.